THE IMPACT OF TECHNOLOGY ON LANGUAGE LEARNING - Akhmadova Maftuna Ibodullo kizi (Research Focus International Scientific Journal, 2025)
Technology has revolutionized language learning by providing innovative tools and resources that enhance the acquisition process. This article examines the impact of technology on different aspects of language learning, including cognitive, social, and emotional factors. It explores how digital platforms, artificial intelligence, and multimedia applications influence language learning across various age groups. The paper also discusses the effectiveness of technology-based language assessments and compares traditional and modern learning methods. By understanding the role of technology in language education, educators can integrate digital tools effectively to improve learning outcomes. The article concludes with practical recommendations for optimizing the use of technology in language learning.